Wikipedia's Influence on the Evolution of Encyclopedia - Librenjak, Sara; Jecić, Zdenko; Boras, Damir (2009)
This article deals with the users of Wikipedia and their usage and opinions re- garding Wikipedia in comparison to printed encyclopedias. A representative sample of high school and university students from Zagreb was surveyed. It is investigated why students tend to use Wikipedia significantly more than printed encyclopedias, even though they are considered more accurate and re- liable, which is important in educational usage. The results of the survey may serve as guidelines for both users and profession- als, i.e. encyclopedists. Various issues with Wikipedia which also need attention in this context, e.g. the development of Croatian Wikipedia, are briefly ad- dressed. The goal of this work is to broaden the awareness of recent phenomena in ency- clopedic, or generally, information science, in order to aid in improvement of encyclopedic products
Projekt MZOS
ENG